2020
DOI: 10.1073/pnas.2009415117
|View full text |Cite
|
Sign up to set email alerts
|

How a B family DNA polymerase has been evolved to copy RNA

Abstract: We report here crystal structures of a reverse transcriptase RTX, which was evolved in vitro from the B family polymerase KOD, in complex with either a DNA duplex or an RNA–DNA hybrid. Compared with the apo, binary, and ternary complex structures of the original KOD polymerase, the 16 substitutions that result in the function of copying RNA to DNA do not change the overall protein structure. Only six substitutions occur at the substrate-binding surface, and the others change domain–domain interfaces in the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…It is intriguing to observe how the DNA-dependent DNA polymerase and the RNA-dependent DNA polymerases are comparable structurally, although we cannot detect similarity in terms of primary sequence [ 23 ]. Another point to keep in mind is that some DNA-dependent DNA polymerases exhibit some reverse transcription activity and that only a few mutations can induce this activity to emerge in DNA-dependent DNA polymerases [ 29 , 30 , 31 ]. These facts, when taken together, may suggest that these two groups of proteins have a common ancestor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is intriguing to observe how the DNA-dependent DNA polymerase and the RNA-dependent DNA polymerases are comparable structurally, although we cannot detect similarity in terms of primary sequence [ 23 ]. Another point to keep in mind is that some DNA-dependent DNA polymerases exhibit some reverse transcription activity and that only a few mutations can induce this activity to emerge in DNA-dependent DNA polymerases [ 29 , 30 , 31 ]. These facts, when taken together, may suggest that these two groups of proteins have a common ancestor.…”
Section: Resultsmentioning
confidence: 99%
“…In the process of replicating the genetic material, they act both in the replication of the genome and in the maturation of the Okazaki fragments, showing different functional versatility of the bacterial polymerases, since in this lineage, there was a specialization of the polymerases C and A for replication and maturation of Okazaki fragments, respectively. Some studies have shown that with a few mutation points, specimens of this family acquired a reverse transcriptase function, which may indicate an evolutionary reversion process, since it is suggested that all families of DNA-dependent DNA polymerases may have had a reverse transcriptase as an ancestral molecule [ 30 ]. In our analysis, sequences from the main groups of Archaea and Eukarya, and viral lineages, were used.…”
Section: Archaeal and Eukaryotic Dna-dependent Dna Polymerasementioning
confidence: 99%
“…KOD DNA polymerase (KOD pol) is an important representative of B family DNA polymerases 24,25 . Since the discovery and isolation of strain KOD1 by Morikawa et al in 1994 26 , an abundant number of related strains and their enzyme products were examined and reported from this archaeon 27,28 . Recombinantly produced KOD DNA polymerases are the key component of numerous biotechnological applications such as PCR 29 , RT-qPCR 30 , multiplex PCR 31 , incorporation of base/sugar modified nucleoside triphosphates 32 , and TNA synthesis 33,34,35 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Because C-terminal ‘thumb’ domains of reverse transcriptase undergo significant conformational changes that are strictly required for polymerase activity ( 17 ), some studies have suggested that the telomerase CTE may also undergo changes from an open to a closed conformation during the catalytic cycle ( 18 ). For example, the study of the dynamics of TERT and TER during catalysis using single-molecule Förster resonance energy transfer (smFRET) ( 19 ), TERT modelling ( 14 ) and based on the structure of TERT in complexes with a BIBR1532 telomerase inhibitor ( 20 ) have suggested that CTE may undergo a conformational change.…”
Section: Introductionmentioning
confidence: 99%